쌍별귀뚜라미 열수 추출물의 대식세포 염증반응 및 NLRP3 인플라마좀 활성화 억제 효과 - 박보미(Bomi Park); 김소연(So Yeon Kim); 김영남(Young Nam Kim); 양승돈(Sung Don Yang); 서원균(Wongyun Seo); 한승연(Seung Yun Han); 유영춘(Yung Choon Yoo) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2022)
쌍별귀뚜라미(Gryllus bimaculatus)는 전 세계 32종의 귀뚜라미 중 유일하게 식용으로 활용 가능한 종으로, 항산화 작용, 항당뇨 효과, 간 기능 회복 등 다양한 생리활성이 지닌 것으로 알려져 있다. 본 연구에서는 쌍별귀뚜라미의 열수 추출물(HW-GB)을 이용하여 RAW 264.7 세포에서의 염증 억제 활성과 골수유래 대식세포(BMDM)에서 NLRP3 활성화 억제에 의한 항염증 활성을 조사하였다. 그 결과 HW-GB은 독성이 없는 농도에서 염증매개인자인 NO를 비롯하여 TNF-α 및 IL-6 등 전염증성 사이토카인의 생성은 물론, NO 합성효소인 iNOS와 TNF-α 및 IL-6의 mRNA 발현도 억제하였다. 한편 HW-GB는 LPS 자극 RAW 264.7 세포 내 신호전달계에 있어서 ERK, JNK 및 p38과 같은 MAPK 효소의 인산화를 현저하게 억제하는 것으로 나타났다. 또한 LPS+ATP로 자극된 골수유래 대식세포 염증반응에 대한 HW-GB의 억제 효과를 조사한 결과, HW-GB는 LPS+ ATP로 자극된 BMDM 세포로부터의 IL-1β 분비를 유의하게 억제하였으며, 이러한 IL-1β 분비 억제 활성은 NLRP3와 ASC 분자의 세포 내 발현억제를 통한 NLRP3 인플라마좀 활성화의 저해에 의한 것으로 밝혀졌다. 종합해 보면 HW-GB은 높은 항염증 활성을 지닌 새로운 바이오 소재로서 염증 관련 질환의 예방과 치료에 유효한 식품 혹은 의약 소재로 응용 가능할 것으로 기대된다. In this study, we investigated the inhibitory effect of the hot-water extract of Gryllus bimaculatus (HW-GB) on the inflammatory responses of lipopolysaccharide (LPS)-stimulated RAW 264.7 cells and bone marrow- derived macrophages (BMDM), and partially demonstrated the intracellular mechanisms related to the anti-inflammatory activity of HW-GB. Treatment with HW-GB significantly inhibited the production of nitric oxide (NO) and pro-inflammatory cytokines such as tumor necrosis factor (TNF-α) and interleukin-6 (IL-6) in LPS-stimulated RAW 264.7 macrophages in a dose-dependent manner. Reverse transcription polymerase chain reaction (RT-PCR) analysis revealed that the expression of TNF-α, IL-6, and iNOS (an NO synthase) mRNAs prominently decreased after the HW-GB treatment. In addition, it was shown that HW-GB inhibited phosphorylation of mitogen-activated protein kinases (MAPKs) such as extracellular signal-regulated kinase 1/2 (ERK), jun N-terminal kinase (JNK), and p38 in LPS-stimulated RAW 264.7 cells. In the analysis of IL-1b production from BMDM stimulated with LPS+ATP, HW-BG significantly reduced IL-1b production in a dose-dependent manner through the downregulation of the expression of NOD-like receptor pyrin domain-containing protein 3 (NLRP3) and apoptosis-associated speck-like protein containing caspase recruitment domain (ASC) molecules. In the confocal analysis, it was also observed that HW-GB inhibited co-localization of both NLRP3 and caspase-1, and NLRP3 and ASC in LPS+ATP-stimulated BMDM. Collectively, HW-GB has a strong anti-inflammatory activity and hence can be considered an effective functional food candidate for the prevention and treatment of inflammation-related immune diseases. KCI Citation Count: 1